Solubility and Permeability Enhancement of active compounds: Therapeutic Deep Eutectic Systems as New Vehicles for Drug Delivery - Duarte, Ana Rita C. (2016)
Therapeutic deep eutectic systems (THEDES) are here proposed as a new class of pharmaceutical active ingredient (API) whose distinctive characteristic is the fact that they are liquid at room temperature. Eutectic systems have been described in the pharmaceutical sciences as an alternative formulation able to enhance bioavailability of the API. THEDES are constituted by one active agent and a coformer or two active agents, which when combined at a particular molar ratio become liquid at room temperature. In this work, we explore the prepararation of the THEDES menthol-ibuprofen. The solubility and dissolution profile in phosphate buffer solution (pH 7.4) was performed at 37Â°C and compared with those of the pure API. Furthermore, the in vitro permeability of the liquid THEDES and the API in powder form, was evaluated using a Franz diffusion cell and caco-2 cells as model of human intestinal epithelium. The solubility of the API's when in the THEDES system improved as much as up to 12 fold. Furthermore, for this system the permeability was calculated to be 14â Ã â 10â 5 cm/s representing a 3 fold increase in comparison with the pure API. The results indicate that both solubilization and permeability were greatly enhanced when the API is complexed in the THEDES liquid form. The results obtained demonstrate the potential of THEDES to overcome the drawbacks of poorly water soluble molecules and increase bioavailability of the APIs and the possibility to develop new delivery systems.